The Student Perception of Football Dribbling Learning Development at SMA Negeri 3 Musi Rawas Utara Regency - Riansyah, Riansyah; Lanos, Muhsana El Cintami; Handayani, Widya (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine students’ perceptions of physical education learning models through games based on (1) Perceptions of football dribbling learning knowledge, (2) Perceptions of teacher teaching styles, (3) Perceptions of the media used are easy to use, (4) Perceptions of interest in learning football dribbling, (5) Perceptions of the need to develop football dribbling learning models. This research is descriptive quantitative research. The results of this study showed that (1) Perception of football dribbling learning knowledge obtained a score of 87.15% in the very good category, (2) Perception of teacher teaching style obtained a score of 74.35% in the good category, (3) Perception of the media used is easy to use obtained a value of 86.67% in the very good category, (4) Perception of interest in learning football dribbling obtained a value of 93.72% in the very good category, (5) The perception of the need to develop a learning model of basic football dribbling techniques obtained a score of 100% in the very good category, which means that students agree if the development of football dribbling learning. The results of this study show that students’ perceptions of the development of football dribbling learning in Senior High Schools in North Musi Rawas Regency are positive, for that it is necessary to develop football dribbling learning.